Referee bias and stoppage time in Major League Soccer: A partially adaptive approach - Katherine G. Yewell; Steven B. Caudill; Franklin G. Mixon (Econometrics, 2014)
This study extends prior research on referee bias and close bias in professional soccer by examining whether Major League Soccer (MLS) referees' discretion over stoppage time (i.e., extra play beyond regulation) is influenced by end-of-regulation match scores and/or home field advantage. To do so, we employ a grouped-data regression model and a partially adaptive model. Both account for the imprecise measurement in reported stoppage time. For the 2011 season we find no home field advantage. In fact, stoppage time is the same with a one or two goal deficit at the end of regulation, regardless of which team is ahead. However, the 2011 results do point to an increase in stoppage time of 12 to 20 seconds for nationally televised matches. For the 2012 season, the nationally televised effect disappears due to an increase in stoppage time for those matches not nationally televised. However, a home field advantage is present. Facing a one-goal deficit at the end of regulation, the home team receives about 33 seconds more stoppage time than a visiting team facing the same deficit.
Keywords: L8; L83; L2; C20; 330; partially adaptive estimation; referee bias; close bias; grouped-data regression